STUDI KASUS KEHIDUPAN MASYARAKAT TRANSPOLRI JAYA GUNA II DI BIDANG EKONOMI DAN SOSIAL BUDAYA DI DESA KOMERING PUTIH KECAMATAN GUNUNG SUGIH TAHUN 1987-1999 - Veri Sandria; Bobi Hidayat (UNIVERSITAS MUHAMMADIYAH METRO, 2021)
The purpose of this study was to find out the history of the life of the Transpolri Jaya Guna II community in 1987-1999, to find out the life of the Transpolri Jaya Guna II community in the economic field in 1987-1999, to find out the life of the Transpolri Jaya Guna II community in the socio-cultural field in 1987. -1999. This research approach is qualitative research. Qualitative research is research that describes an event or phenomenon that exists in the social sphere. The presence of researchers as a means of collecting data and analyzing it. The data in this study were collected by interview and observation methods. Data analysis in this study used descriptive data analysis, namely data reduction, data presentation, and reporting of results. The Conclusion of this study indicate that the background of the Jayaguna II Transpolri is the success of the Jayaguna I Transpolri in distributing the welfare of members of the Police. The motive of Transpolri Jayaguna II is to improve the welfare of citizens, where residents of Transpolri Jayaguna II are retirees from the National Police. Because the pension funds provided could not meet their needs, the residents were transmigrated to the Lampung area by being given agricultural land. The social life of Transpolri Jayaguna II residents in 1987-1999 was well established. Along with its development, the population of Transpolri Jayaguna II increased until it reached 1690 families. The cultural conditions in Transpolri Jayaguna II are that the existing culture of the community consists of various tribes, the main livelihoods of which are farming, raising livestock and retirees. Residents of Transpolri Jayaguna II also have various religions, such as Islam, Catholicism, and Hinduism.